2021
DOI: 10.1007/s10008-021-05015-8
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion analysis of graphite sinter as bipolar plates in the low-temperature PEM fuel cell simulated environments

Abstract: The article presents the results of research and an analysis of the possibility of using sinters made of graphite powder as a material dedicated to the production of bipolar plates for low-temperature fuel cell. The use of powder metallurgy technology allows for the production of materials that meet the requirements for fuel cell elements for the construction of elements closing a single cell (bipolar or monopolar plates) or interconnectors. The morphological and chemical analysis of graphite powder, microstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Several past works investigated graphite and various carbon‐polymer nanocomposites as preferable substitutes for metallic BPs [31,103–105] . Recent work showed that the sinters made of commercial graphite powder had high corrosion resistance in simulated PEMC conditions [106] …”
Section: Fuel Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several past works investigated graphite and various carbon‐polymer nanocomposites as preferable substitutes for metallic BPs [31,103–105] . Recent work showed that the sinters made of commercial graphite powder had high corrosion resistance in simulated PEMC conditions [106] …”
Section: Fuel Cellsmentioning
confidence: 99%
“…[31,[103][104][105] Recent work showed that the sinters made of commercial graphite powder had high corrosion resistance in simulated PEMC conditions. [106] Carbon nanofibers (CNFs) and CNTs could act as excellent fillers to the conducting polymer-based composites, enhancing the mechanical properties and corrosion resistance considerably. [107] EIS studies on a carbon black (CB)-synthetic graphite-polyvinylidene fluoride (PVDF) composite in simulated PEMC conditions showed that when the CB content in the composite exceeded 5 wt %, the corrosion resistance started to decline.…”
Section: Carbon-based Compositesmentioning
confidence: 99%
“…The materials that are most commonly used to fabricate BPs are categorized into metallic and non-metallic (carbon-based) substances [62]. Non-porous graphite is usually used in laboratory applications due to its high electrical and thermal conductivity, chemical stability, and resistance against corrosion and gas permeation [63]. However, the mechanical properties of graphite are not interesting, and its manufacture is expensive.…”
Section: Protective Coating Of Bipolar Platesmentioning
confidence: 99%
“…According to the different material classifications, BPs can be divided into graphite BPs, metal BPs, and resin/graphite composite BPs. Graphite BPs have good electrical conductivity, thermal conductivity, and corrosion resistance [8]; however, their mechanical properties are poor, and the graphite BPs with flow channels are costly. In addition, graphite BPs have a low gas transmission rate [9].…”
Section: Introductionmentioning
confidence: 99%